2007
DOI: 10.1158/0008-5472.can-06-2698
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MicroRNA Expression Levels and Their Biological Correlates in Human Cancer Cell Lines

Abstract: MicroRNAs are small noncoding RNAs that function by regulating target gene expression posttranscriptionally. They play a critical role in developmental and physiologic processes and are implicated in the pathogenesis of several human diseases including cancer. We examined the expression profiles of 241 human microRNAs in normal tissues and the NCI-60 panel of human tumor-derived cell lines. To quantify micro-RNA expression, we employed a highly sensitive technique that uses stem-loop primers for reverse transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
524
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 665 publications
(572 citation statements)
references
References 50 publications
41
524
2
5
Order By: Relevance
“…Microarray studies have characterized the modulation of miRNA expression in prostate cancer as compared with normal prostate tissue and identified a number of miRNAs that are up-or downregulated in prostate tumors (Jiang et al, 2005;Mattie et al, 2006;Volinia et al, 2006;Gaur et al, 2007;Porkka et al, 2007;Ozen et al, 2008). In all of these studies, miRNA expression profiles were based on the current databases of miRNAs known at the time (Volinia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray studies have characterized the modulation of miRNA expression in prostate cancer as compared with normal prostate tissue and identified a number of miRNAs that are up-or downregulated in prostate tumors (Jiang et al, 2005;Mattie et al, 2006;Volinia et al, 2006;Gaur et al, 2007;Porkka et al, 2007;Ozen et al, 2008). In all of these studies, miRNA expression profiles were based on the current databases of miRNAs known at the time (Volinia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of miRNA expression has been identified in a number of cancers (Pan et al, 2001;Lu et al, 2005;Volinia et al, 2006;Blenkiron et al, 2007;Chen and Stallings, 2007;Fulci et al, 2007;Gaur et al, 2007;Kummar et al, 2007;Meng et al, 2007;Porkka et al, 2007;Wedel et al, 2008) and an accumulating data indicate that some miRNAs can function as tumor suppressors or oncogenes and are important in cancer development. Deletion or loss of function of a tumor-suppressing miRNA results in overexpression of target oncogenes.…”
Section: Introductionmentioning
confidence: 99%
“…Independent research groups have reported significant miRNA alteration in glioma by profiling (Gaur et al, 2007;Malzkorn et al, 2010). Among these aberrant miRNAs in malignant glioma, miR-124 and miR-128 are better characterized.…”
Section: Discussionmentioning
confidence: 99%
“…3 In melanoma, miRNAs can be readily analyzed from formalin-fixed paraffin-embedded tissue, 4 show high frequency genetic alterations, 5 and exhibit a melanoma-specific signature. 6 In addition, miRNAs have shown prognostic value in melanoma. [7][8][9][10][11] A panel of six miRNAs was identified as a post-recurrence survival signature, 9 and miRNA and mRNA networks were associated with the outcome, 11 while a 4-miRNA signature was associated with brain metastasis.…”
mentioning
confidence: 99%